2021
DOI: 10.4062/biomolther.2020.215
|View full text |Cite
|
Sign up to set email alerts
|

Cell Autonomous Circadian Systems and Their Relation to Inflammation

Abstract: All living beings on earth have an important mechanism of 24-h periodicity, which controls their physiology, metabolism, and behavior. In humans, 24-h periodicity is regulated by the superchiasmatic nucleus (SCN) through external and environmental cues. Peripheral organs demonstrate circadian rhythms and circadian clock functions, and these are also observed in cultured cell lines. Every cell contains a CLOCK: BMAL1 loop for the generation of circadian rhythms. In this review, we focused on cell autonomous cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 103 publications
0
8
0
Order By: Relevance
“…Immune functions such as leukocyte homing, and innate immunity responses also show circadian variations along with the components of immune system. Supporting the fact, it has been observed that IL-1 and IL-6 are only detectable during 12:00-3:00 am in the serum of healthy individuals [79]. Such rhythms have been equally seen in both males and females.…”
Section: Discussionmentioning
confidence: 69%
“…Immune functions such as leukocyte homing, and innate immunity responses also show circadian variations along with the components of immune system. Supporting the fact, it has been observed that IL-1 and IL-6 are only detectable during 12:00-3:00 am in the serum of healthy individuals [79]. Such rhythms have been equally seen in both males and females.…”
Section: Discussionmentioning
confidence: 69%
“… 33 Inflammatory factors could affect peripheral clock activity and the phase, period, and amplitude of expression of circadian clock genes in normal lung tissue were changed by exposure to cigarette smoke, viral or bacterial infection. 34 , 35 In addition, hormonal or autonomic nerve activity synchronized peripheral clocks to the suprachiasmatic nucleus rhythm and affect the asthma activity. 36 The aberrant hormone secretion or autonomic nerve activity might desynchronize peripheral clock rhythm and might affect the airway activity and allergic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…36 Per2 gene regulates daily IL-1β production in macrophages and IFN-γ production in NK cells, altered Per2 gene thus leads to the impairment of immune function. 35 The majority of asthmatic patients have an allergy reaction and several studies showed the circadian disruption can promote allergy. 24,[37][38][39] The mechanism might relate to circadian gating of epithelial barrier function and immune responses that evolved to complex environmental physical, chemical, and biological stimulants and enhance host defense after exposure of stimulants.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the production of the pro-inflammatory cytokines, including interleukin IL-6 and TNF-alpha, exhibit diurnal rhythmicity that correlates inversely with plasma cortisol [ 75 , 76 ]. Indeed, earlier studies on diurnal variation of cytokines reported that cytokine levels were highest in blood taken in the early morning or late evening [ 77 , 78 ]. In this study blood samples were collected between 8 a.m. and 5 p.m. as in the study by Kupper et [ 65 ].…”
Section: Discussionmentioning
confidence: 99%